Collision avoidance path for pedestrian agent performing tawaf - Shuaibu, A.N. (Springer Verlag, 2014)
Collision is one of the major problems affecting the flow of pedestrian in a dense environment. The case study of this research work is the ground flow of Tawaf area (Mataf) at Masjid Al-Haram, Saudi Arabia. We propose a spiral model, that simulates the movement of 1000 agents toward a unify direction while ensuring minimal collision among pedestrians during Tawaf. Based on our findings the spiral path movement is recommended for Tawaf movement. Several simulation trials were run. Outcomes such as average speed, duration and density were computed for different combination of spiral turn. Â© Springer Science+Business Media Singapore 2014.